5-Bromo-2-hydroxybenzene-1,3-dicarbaldehyde - Duclos, Severine; Therrien, Bruno; Ward, Thomas R. (My University, 2001)
In the crystal structure of the title compd., C8H5BrO3, two mols. are linked about inversion centers by C-H...Br H bonds. The structure is also characterized by intra- and intermol. H bonds between hydroxyl and aldehyde O atoms. Crystallog. data are given. [on SciFinder(R)]
Keywords: mol structure bromo hydroxy benzenedicarbaldehyde